A Comparative Analysis of Different Clustering Approaches for Software Process Improvement - Rana, Rajni; Suri, Dr. P.K. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Software development team tries to increase the software quality by decreasing the number of defects as much as possible. Number of defects remaining in a system provides an insight into the quality of the system. Software defects are one of the major factors that can decide the time of software delivery. The proposed system will analyze and categorize the software defects using some cluste ring approach and then the software defects will be measured in each clustered separately. Clustering is the process to present the data in an effective and organized way. There are number of existing clustering approaches but most of them suffer with problem of data distribution. If the distribution is non linear it gives impurities in clustering process. The proposed work is about to use defect prevention for process improvement with the help of clustering algorithms.